GAMBAR CADAS MOTIF MANUSIA DI SITUS BUKIT BULAN, SAROLANGUN, JAMBI - Eric Pradana Putra; Karina Arifin (Balai Arkeologi Provinsi Sulawesi Selatan, 2022)
Recent research in Sumatra has succeeded in finding rock art in several caves and niches in the Bukit Bulan karst area, Sarolangun, Jambi. In this region, rock art with human motifs is present in many shapes and styles. This research discusses the variation of human motifs found in nine caves at the Bukit Bulan region through an analysis of the inherent attributes. Furthermore, the human motif were compared with similar motifs from West Sumatra and Lenggong Valley, Malaysia. The comparisons are made based on the consideration of the proximity of the locations and cultural backgrounds. In addition, the shape and color of the motifs of these three regions are relatively similar, leading to the supposition that the chronology of rock art with specific motifs of humans comes from the same period. This research concludes that the shape of human motifs in Bukit Bulan is more varied than human motifs in West Sumatra and Lenggong Valley. The relative chronologu based on the existence of motifs that are thought to have come from a younger period such as Arabic and Latin makes the assumption that the rock art in Bukit Bulan is not older. This condition is also found at sites in West Sumatra which are associated with Arabic and in the Lenggong Valley which have depictions of motifs from the modern period. Penelitian terbaru di wilayah Sumatra berhasil menemukan gambar cadas pada beberapa gua dan ceruk di wilayah karst Bukit Bulan, Sarolangun, Jambi. Pada wilayah ini gambar cadas bermotif manusia cukup banyak ditemukan dalam bentuk dan gaya yang beragam. Penelitian ini membahas variasi motif manusia yang ditemukan pada sembilan gua di Situs Bukit Bulan melalui analisis atribut-atribut yang melekat. Selanjutnya, motif manusia dibandingkan dengan motif sejenis dari situs-situs di Sumatra Barat dan Lembah Lenggong, Malaysia. Perbandingan tersebut dilakukan atas pertimbangan kedekatan lokasi dan latar belakang budaya pada ketiga wilayah tersebut. Selain itu, bentuk dan warna motif juga relatif serupa, sehingga memunculkan dugaan bahwa kronologi gambar cadas dengan motif spesifik berupa manusia berasal dari masa yang sama. Penelitian ini menghasilkan kesimpulan bahwa secara bentuk motif manusia di Bukit Bulan lebih variatif dibandingkan dengan di Sumatra Barat dan Lembah Lenggong. Kronologi relatif berdasarkan keberadaan motif yang diduga berasal dari masa yang lebih muda seperti tulisan arab dan latin menjadikan dugaan waktu pembuatan gambar cadas di Bukit Bulan tidak lebih tua. Kondisi tersebut ditemukan juga pada situs di Sumatra Barat yang berasosiasi dengan tulisan-tulisan arab serta situs di Lembah Lenggong yang memiliki penggambaran motif dari masa modern.